2022
DOI: 10.1007/s00221-022-06385-9
|View full text |Cite
|
Sign up to set email alerts
|

No self-advantage in recognizing photographs of one’s own hand: experimental and meta-analytic evidence

Abstract: Visually recognising one’s own body is important both for controlling movement and for one’s sense of self. Twenty previous studies asked healthy adults to make rapid recognition judgements about photographs of their own and other peoples’ hands. Some of these judgements involved explicit self-recognition: “Is this your hand or another person’s?” while others assessed self-recognition implicitly, comparing performance for self and other hands in tasks unrelated to self-other discrimination (e.g., left-versus-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…That is, each response to the delay question is a combination of actual perceptual discriminability and an individual criterion, with which participants judge outcomes to be delayed or not. Issues regarding the impact of individual criteria and response biases on behavioural data have, for instance, been discussed in the context of self-identification tasks in previous research 51 . In case of this study, we cannot distinguish between both effects and thus, reported behavioural recalibration effects might be a combined recalibration of perceptual discriminability and the individual criterion.…”
Section: Discussionmentioning
confidence: 99%
“…That is, each response to the delay question is a combination of actual perceptual discriminability and an individual criterion, with which participants judge outcomes to be delayed or not. Issues regarding the impact of individual criteria and response biases on behavioural data have, for instance, been discussed in the context of self-identification tasks in previous research 51 . In case of this study, we cannot distinguish between both effects and thus, reported behavioural recalibration effects might be a combined recalibration of perceptual discriminability and the individual criterion.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these findings cannot fully explain the controversial results in implicit and explicit self-body recognition. More recently, based on meta-analysis and experimental evidence, Holmes and colleagues even suggested that hand recognition may have no self-advantage ( Holmes et al, 2022 ). Thus, it remains unclear whether and how self-advantage exists in body recognition.…”
Section: Introductionmentioning
confidence: 99%
“…However, they may need multiple clues (features) to confirm that the images represent their own hands and then make the positive (“Self”) decision since others’ hands may also display one or more similarities to their own hands. Indeed, research has shown that participants are more likely to make “not their own” judgments, especially when the task is difficult, e.g., with shorter presentation times ( Holmes et al, 2022 ). In this context, the advantage of making a “no” decision (recognizing the hand on the screen as not one’s own) leads to the advantage for “other” judgments, which may be interpreted as self-disadvantage in the explicit task.…”
Section: Introductionmentioning
confidence: 99%